Analysis of the Factors Influencing an Enhance Productivity of Lecturers in Batam City - Indrayani Indrayani; Damsar Damsar (Budapest International Research and Critics University, 2022)
The purpose of this study was to investigate the effect of the work environment and self-efficacy both partially and simultaneously on the work productivity of lecturers at the Universities in Batam City. The analysis employed is associative analysis, and the research method is quantitative, in which the sample includes lecturers at four universities in Batam City, including Universitas Batam, Universitas Ibnu Sina, Universitas Universal, and Universitas Riau Kepulauan. The sampling methodology employs the stratified random sampling technique, a sampling method that takes into consideration the levels or strata in the population. This technique is used when the population comprises members or elements that are not homogeneous and stratified proportionally such that each stratum must be represented in the sample. Samples were collected from each of the two study programs at each institution, namely, Management and Accounting, with the functional position group of Head Lecturer with Lecturer, therefore the number of samples in this study was 40 respondents. The findings of this study show that: 1) the work environment has a partial and significant effect on work productivity; 2) self-efficacy has a partial and significant effect on work productivity; and 3) the work environment and self-efficacy both have a positive and significant effect on work productivity. The adjusted R square value of 0.884 can be called the coefficient of determination. This indicates 0.884 (84.4 percent) of work productivity may be gained and described by the work environment and self-efficacy. The other 15.6% can be explained by variables outside the model that were not explored.